2022
DOI: 10.1371/journal.pntd.0010469
|View full text |Cite
|
Sign up to set email alerts
|

A mixed-methods approach to understanding domestic dog health and disease transmission risk in an indigenous reserve in Guyana, South America

Abstract: Domestic dogs (Canis lupus familiaris) can transmit a variety of pathogens due to their ubiquitousness in urban, rural and natural environments, and their close interactions with wildlife and humans. In this study, we used a mixed-methods approach to assess the role of domestic dogs as potential intermediaries of disease transmission from wildlife to humans among indigenous Waiwai in the Konashen Community Owned Conservation Area, Guyana. To address these objectives we 1) performed physical examinations and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…In Guyana, another Amazonian country, a recent study on various diseases in a southern indigenous Waiwai reserve showed that only one of 20 dogs surveyed (5.0%) had antibodies against L. infantum . The dog in question had been brought as an adult from northwestern Brazil and may have been infected elsewhere ( 37 ). Since dogs have been recognized as a major reservoir for L. infantum infections, the study shows the importance of dog movement among indigenous communities, particularly along international borders ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Guyana, another Amazonian country, a recent study on various diseases in a southern indigenous Waiwai reserve showed that only one of 20 dogs surveyed (5.0%) had antibodies against L. infantum . The dog in question had been brought as an adult from northwestern Brazil and may have been infected elsewhere ( 37 ). Since dogs have been recognized as a major reservoir for L. infantum infections, the study shows the importance of dog movement among indigenous communities, particularly along international borders ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…The dog in question had been brought as an adult from northwestern Brazil and may have been infected elsewhere ( 37 ). Since dogs have been recognized as a major reservoir for L. infantum infections, the study shows the importance of dog movement among indigenous communities, particularly along international borders ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is enough evidence (e.g., the presence of sand fly vectors, human cases, and/or seropositive dogs) indicating the risk of canine leishmaniasis in these countries [ 27 30 ]. For instance, leishmaniasis is considered nonendemic in Chile, but supposedly, imported cases in humans [ 31 ] and seropositive dogs [ 29 , 30 ] have been reported. Little is known about the sand fly fauna of Chile, where only a single sand fly species ( Oligodontomyia isopsi ) has been reported thus far [ 32 ].…”
Section: Geographical Distributionmentioning
confidence: 99%
“…The new SARS-CoV-2 [47] thus reminds us that cross-species transmission depends significantly on the different modalities of human existence; our presence in the material world is, properly speaking, inextricably intertwined with other entities and hence, chaotic outcomes are highly contingent upon the quality of the human-environment interface. Zoonoses, in essence, are the byproduct of the entangled and intricate relationships among humans, different animal taxa, and their econiches [48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%